NK cell-based immunotherapy strategies for myeloid leukemia - Zhang, Lin; Zhao, Yibo; Dong, Yan; Jiang, Xiuxing (Frontiers in Immunology, 2025)
Myeloid leukemia (ML) is a clonal malignant disease with abnormal hematopoietic stem cells. With the emergence of novel immunotherapies, such as CAR-T, therapeutic outcomes in ML patients have improved, while significant challenges persist, including severe adverse events and disease recurrence. Natural killer cells (NK cells) are “natural killers” of the immune system that do not require antigen presentation and responsible for recognizing and destroying tumor cells. Some NK cells-based clinical experiments have been carried out and achieved remarkable results with lower side effects in ML. Crucially, within the ML microenvironment, NK cells frequently exhibit more severe functional exhaustion compared with T cells, characterized by impaired cytotoxicity, cytokine production, and proliferative capacity which limits anti-ML efficacy of NK cells. However, clinical studies utilizing NK cell-based therapies (e.g., adoptive transfer, CAR-NK cells) have demonstrated promising results with favorable safety profiles, underscoring their therapeutic potential. Therefore, developing more strategies based on NK cell is of great clinical significance for the treatment of ML. In this review, we systematically analysed the relationship between ML and NK cells, aiming to propose more novel protocols for NK cell expansion and persistence enhancement, establish evidence-based guidelines for next-generation NK cell-based immunotherapies in ML treatment.